The Level Of Students’ Anxiety In Speech At Stikes Paluta Husada Gunung Tua - Yulina Oktaviani Harahap (Departement of Mathematics Education, 2023)
The research' goal is to evaluate the students' levels of anxiety across their five semesters of midwifery courses at STIKes Paluta Husada. A descriptive quantitative research design was adopted for this study. A straightforward statistical method was used to notify and present the data obtained in a descriptive manner. Twenty-five randomly selected midwifery students made up the study's subject group. The Foreign Language nervousness Scale (FLAS) measures students' degree of nervousness by having them take a speaking exam before giving their speech. After that, a questionnaire for this study was created based on Horwitzh's FLAS (The Foreign Language Anxiety Scale). Concerns about communication, exam anxiety, and fear of receiving a poor evaluation are among the 33 questions on the Foreign Language Anxiety Scale (FLAS), which were separated into three categories. According to this study, 98.2% of the pupils were classified as intermediate anxious, 9.2% as anxious, and 115.3% as having extremely high levels of anxiety. According to the findings, there were no students who were extremely relaxed or at a degree of relaxation. According to the study's findings, the majority of pupils experienced quite severe speech anxiety.